Parenting style and the active involvement of fathers in child-rearing - Brust Nemet, Maja (Array, 2021)
The active involvement of fathers in child-rearing affects the child"s overall growth and development, and the parenting style impacts the direction of the influence on individual aspects of a child"s life. In order to achieve gender equality in society, it is necessary to raise public awareness of the importance of a father"s gender role, a desirable parenting style, and his inclusion in all aspects of family life. The aim of the research is to determine the level of father involvement in child-rearing, as well as the dominant parenting style based on the children"s assessment. A total of 290 pupils from 10 elementary schools in Osijek-Baranja County participated in this research, all of whom were in grades 5-8. Sociodemographic data, the 2018 parent involvement questionnaire - URU18, and the parenting behavior questionnaire 29 - URP29 were used. The results are in line with research conducted so far, and they indicate the importance of a father"s education and a supportive parenting style aiming at his involvement  in housework and child care. Father"s education significantly presupposes his involvement in housework, taking care of school-related duties and obligations, and participation in leisure activities. A supportive parenting style is a significant positive predictor of all forms of father involvement, i.e., housework, school-related duties and obligations, activities, child care, and counseling. The results of this research indicate the importance of raising parental awareness of the importance of the supportive parenting style and the fathers" involvement in child-rearing.